Multiple Activation Catalyst for Asymmetric [4+2] Cycloaddition of Aldehydes with Dienes - Tomifuji, Rei; Murano, Shunpei; Teranishi, Satoru; Kuroda, Daiki; Kurahashi, Takuya; Matsubara, Seijiro (Synlett, 2021)
The enantioselective oxa-Diels–Alder reaction of nonactivated substrates by utilizing FeCl3 and a 1,1′-bi-2-naphthol (BINOL) derived chiral phosphoric acid as a multiple activation catalyst is reported. Various oxygen-containing six-membered heterocycles were obtained in high yields and in an enantioselective manner. Density functional theory (DFT) calculations elucidate that both Lewis acidic and Brønsted acidic moieties in the catalyst system synergistically activate two lone pairs of an aldehyde to facilitate enantioselective addition reaction of dienes.
Keywords: operando XAFS; DFT; iron; asymmetric cycloaddition; Diels–Alder